Gigantic Ruptured Aneurysm of the Gastroduodenal Artery Successfully Treated by Coiling - Nguyen, An Tuyet (EJVES Short Rep, 2019)
INTRODUCTION: Visceral aneurysms are rare and a life threatening condition in the case of rupture. REPORT: A 78 year old woman presented with sudden brief loss of consciousness and complained of abdominal tenderness on examination. Computed tomography revealed a gigantic 100 × 130 × 200 mm ruptured true aneurysm of the gastroduodenal artery, which was successfully treated by endovascular coiling. Post-operative observation was uneventful and the six week follow up duplex ultrasound confirmed absence of luminal flow in the aneurysm. DISCUSSION: The treatment threshold of visceral aneurysms and treatment modalities are reviewed.